No regression of renal AL amyloid in monoclonal gammopathy after successful autologous blood stem cell transplantation and significant clinical improvement - Zeier, Martin; Dengler, Jolanta; Linke, Reinhold P.; Donini, Ugo; Waldherr, Rüdiger; Andrassy, Konrad; Ho, Anthony Dick; Goldschmidt, Hartmut (Nephrology, dialysis, transplantation, 2003)
Background. High-dose chemotherapy followed by autologous blood stem cell transplantation induces remission of plasma cell dyscrasia in patients with AL amyloidosis. The impact of this treatment on the glomerular amyloid mass is still unknown.Methods. In the present study, the quantity of the renal amyloid mass before and more than 3 years after high-dose melphalan treatment and autologous blood stem cell transplantation was assessed in two patients. At the time of the second renal biopsy, both patients were in complete remission without detectable serum and urinary monocloncal IgA-λ and a normal percentage of plasma cells in the bone marrow.Results. In both patients with biopsy-proven AL amyloidosis, urinary protein excretion decreased from 7 g/24 h to <2 g/24 h more than 3 years after autologous blood stem cell transplantation. In contrast, glomerular amyloid deposits persisted, as shown in the second biopsy.Conclusion. Despite complete remission of the plasma cell dyscrasia and improvement of glomerular permeability, the amount of glomerular amyloid mass did not regress.